HUBUNGAN PENGETAHUAN IBU DAN DUKUNGAN SUAMI TERHADAP KEPATUHAN IBU HAMIL MELAKUKAN ANC DI KLINIK MITRA ANANDA PALEMBANG TAHUN 2023 - Dona Tri Sundari; Nurbaity; Untari Anggeni (LPPM STIKes Mitra Adiguna, 2023)
The low knowledge of mothers about antenatal care causes low participation of mothers in making pregnancy visits. With this knowledge of antenatal care, it is hoped that the mother will be strongly motivated to take care of herself and her pregnancy, so that the mother can pass her pregnancy well and produce healthy babies. Husband's support in antenatal care can be shown by taking his wife to check during pregnancy. The success of antenatal care visits must also be supported by great compliance from pregnant women themselves. The purpose of this research was to determine the relationship between knowledge and husband's support for pregnant women's compliance with antenatal care visits. The sample in this research were all third trimester pregnant women who had their pregnancy checked. The scope of this research is the adherence of pregnant women to antenatal care. The design in this research uses an analytical design with a Cross Sectional approach and the number of samples is 30 people. The results obtained from the chi-square test obtained p = 0.009 <a 0.05, then there is a relationship between knowledge and compliance with pregnant women who perform ANC and p = 0.006 <a 0.05, then there is a relationship between husband's support and compliance with pregnant women who do ANC. Suggestions to midwives can continue to improve counseling, information and education to pregnant women about the importance of doing ANC regularly.